Are We Comparing Yet? - Saussy, Haun (BiUP General, 2019)
Debates about the possibility of an open culture – or indeed about the possibility of an open debate about the openness of culture – often turn on questions of standards. But since no benchmark can be absolute, judgement is a proliferation of comparisons. Through a series of case studies in everyday and academic comparison (literature, history, politics, philosophy), Haun Saussy calls out the typical vices of comparison and proposes ways to unseat them. For however much it is abused, distorted, and manipulated, comparison retains an essential link to the idea of justice.